EXPLORING CORN STARCH-BASED BIODEGRADABLE PLASTICS FOR FOOD PACKAGING APPLICATIONS - Nur Syahida Abdul Rahim; Liyana Karmila Noazman; Mohd Muzammir Firdaus Abu Bakar, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Recently, there has been growing interest in the use of biodegradable plastics made from corn starch to enhance environmental sustainability. This study explores the potential of biodegradable plastics to foster eco-friendly practices and serve as alternatives to traditional plastics as food packaging. The study focuses on developing a packaging solution by leveraging the unique properties of hydrogels combined with corn starch in different ratios to create durable biodegradable plastics. Additionally, the study evaluates the impact resistance and rebound characteristics of hydrogel-based packaging materials using the coefficient of restitution (COR), which measures the elasticity of collisions. By assessing the mechanical properties and potential uses of hydrogels with varying corn starch content, this research aims to identify formulations that balance functionality, environmental impact, and sustainability. The study’s findings show hydrogel with the largest percentage of cornstarch (20%) exhibits the best outcome as a reliable and efficient biodegradable plastic to traditional plastic. Future research is recommended to explore the properties of biodegradable plastic in analysis including examining mechanical strength, barrier properties, and degradation rate.